Telaah Challenge Based Learning (CBL) Bernuansa Etnomatematika Berbantuan Instagram terhadap Kemampuan Berpikir Kreatif Matematis - Muhammad Ghozi Izzulhaq; Adi Satrio Ardiansyah (Institut Agama Islam Negeri Curup, 2023)
Mathematical creative thinking ability is an important aspect in facing the era of disruption. Based on the results of PISA and TIMSS studies, the mathematical creative thinking ability of students in Indonesia is still low. Challenge Based Learning (CBL) presents an alternative solution to address this problem. On the other hand, ethnomathematics and instagram will bring their own meaningfulness to students' learning. The innovation of CBL with an ethnomathematics nuance, supported by instagram, becomes one alternative in developing mathematical creative thinking abilities. This study aims to describe the effect of CBL with an ethnomathematics nuance supported by instagram on mathematical creative thinking ability through a literature review. The literature review analysis was conducted on relevant national and international studies. The facts show that the use of CBL models makes students more creative and innovative, thus developing their mathematical creative thinking ability. The CBL framework integrated with ethnomathematics supported by instagram will provide a unique learning significance for students. The results of the literature review indicate that the innovative CBL model with an ethnomathematics nuance supported by instagram can have a positive impact on students' mathematical creative thinking ability.